Interesting rare case of recurrent puerperal uterine inversion: a case report - Kharkwal, Sushila; Jain, Divya; Agarwal, Sippy; Pandey, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine inversion is a rare obstetric emergency that may lead to severe haemorrhage, shock and eventually death. The incidence of uterine inversion varies from one in 2,000-20,000 deliveries. Recurrent uterine inversion is still rare with no exact reported incidence so far. We report a case of a near miss patient, 28 years old primiparous with complete uterine inversion with atonic postpartum haemorrhage and shock, managed by manual repositioning and tamponade insertion which got corrected. Patient had recurrent uterine inversion twice in the puerperal period on 5th and 7th postpartum day. A new approach to management was taken. Rather than going for laparotomy, vaginal manual correction followed by intrauterine tri-way foley catheter insertion was done. Gradual deflation was done leading to final permanent correction. Uterine inversion is a rare but potentially deadly complication post vaginal delivery. Mortality and morbidity can be reduced by rapid recognition and immediate replacement. For recurrent inversion prolonged intrauterine balloon placement may be needed in rare cases.